EVALUATING PHARMACY TECHNICIANS’ KNOWLEDGE AND ATTITUDES TOWARD MEDICATION SAFETY AND ERROR PREVENTION: A SURVEY STUDY - Fawzeyah saleem Aldafiri•, ‏Mashael hamud AL shammary, ‏Manal Marzook Alshammary, ‏Kholoud mohsen alenazi, ‏Anood Rabaah Alshammary, ‏Ikhlas Rabah Alshammar (Chelonian Research Foundation, 2022)
Medication errors are a major patient safety issue. Pharmacy technicians play a crucial role in dispensing processes, yet limited research evaluates their capabilities around safe practices. This study surveyed 254 pharmacy technicians across 5 hospitals in Saudi Arabia assessing knowledge and attitudes related to medication safety using a validated instrument. Results revealed moderate baseline knowledge regarding error types, risk factors, prevention strategies and reporting procedures (average score of 67% correct). Technicians showed generally positive safety attitudes, although scores were lower around fear of consequences for errors and ability to oppose unsafe prescribing. Supervisors had better knowledge but not attitude scores. Targeted education and training to correct misconceptions, along with improved safety culture fostering accountability without blame, can enhance this vital workforce's preparedness to reduce medication error risks. Keywords: medication safety; pharmacy technicians; knowledge; attitudes; survey